Learning Strategy Implementation in Storytelling-based Training to Enhance Early Childhood Teachers’ Instructional Skills - karnedi Karnedi; Lisda Hendrajoni (Pengabdian Masyarakat Sumber Daya Unggul, 2026)
This study employed a descriptive, quantitative program evaluation design to assess the effectiveness of training in storytelling-based learning strategies for early childhood teachers. The evaluation adopted a logic model framework comprising four components: input, process, output, and outcome. Data were collected through a structured evaluation instrument, a five-point Likert-scale satisfaction questionnaire, and open-ended questions completed by kindergarten teachers participating in the training. Descriptive statistics, including mean scores, were used to analyze quantitative data, while qualitative responses explored participants’ perceptions. The findings showed that the training was highly effective and positively received. Participants reported high satisfaction with the training materials (M = 4.38), lecturer capability (M = 4.51), training methods (M = 4.18), and learning strategy (M = 4.47). They valued the relevance of the materials, interactive learning activities, and the lecturer’s supportive approach. Open-ended responses indicated that storytelling demonstrations, collaborative discussions, and practical simulations enhanced teachers’ creativity, communication skills, and pedagogical competence. Overall, the training effectively strengthened instructional competence and promoted engaging, child-centered learning in early childhood education.